THE EFFECT OF GIVING NATURAL GUARD ESSENTIAL OIL IN DRINKING WATER ON BLOOD UREA NITROGEN LEVELS, CREATININE, AND AMINOTRANSFERASE IN BROILERS - Muhamad Abdul Shidiq; Ida Bagus Komang Ardana; I Ketut Sumadi; I Made Merdana; Luh Made Sudimartini; Yousef Haig Setrak Babikian; Haig Yousef Babikian; Rubiyanto Widodo Haliman; Kristina; Theng In Yen; Hendi Yanto Efendy (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
To increase growth and feed efficiency, we can use feed additives through feed or drinking water, one of which is the use of essential oils. NATURALGUARD is a mixture of natural oils, namely pine oil (Pinus sp.), lavender (Lavandula sp.), and eucalyptus oil (Eucalyptus sp.) which contains active compounds as immunomodulators, antibacterials, antioxidants, anti-inflammatory, antifungal and antiviral. This study aims to determine the level of Blood Urea Nitrogen (BUN), Creatinine, Aspartate Aminotransferase (AST), and Alanine Aminotransferase (ALT) in broilers after being given NATURALGUARD via drinking water. This study used a completely randomized design with a total sample of 24 broiler CP-707 strain, with four treatments and six replications. The treatment applied was P0 as a control without giving NATURALGUARD, P1 P2, and P3 were given NATURALGUARD at doses of 1, 2, and 4 g/L respectively, adlibitum for 30 days. At the end of the study, 3 mL of blood sample was taken via the pectoral vein aseptically, and then a blood serum examination was carried out. The research results showed that the highest mean BUN level was at P0 (8.9 mg/dL) and the lowest was at P1 (5.2 mg/dL), the highest creatinine was at P3 (1.08 mg/dL) and the lowest was at P0 and P1 (1, 0 mg/dL), AST was highest at P0 (273 µ/L) and lowest at P2 (220 µ/L), and ALT was highest at P0 (7.5 µ/L) and lowest at P3 (5.48 µ/ L). Statistical results showed no significant differences in BUN, creatinine, AST, and ALT levels in all treatment groups. It was concluded that NATURALGUARD as feed additive at doses of 1, 2, and 4 g/L via drinking water is safe to be used in broilers.